MANEJO DE PLATAFORMAS INFORMÁTICAS EN EL GOBIERNO AUTÓNOMO DESCENTRALIZADO MUNICIPAL DEL CANTÓN VINCES - Triana Bustamante, Cristhian Lauriano (2019)
The type of research that is used is the exploratory because through this research it is possible to know about the setbacks that occur in the department of Guardalmacén of the GADMCV, consequently, the methods that were used in the research are: the analytical method, focuses In knowing the reality of the company with the purpose of examining all the events that happen in this department, the descriptive method is described in detail the facts generated in the company from the presented problems and the bibliographic research